Pengaruh Kecerdasan Emosional Dan Keterampilan Kepemimpinan Situasional Terhadap Kinerja Pengelola Program Pasca Sarjana (Studis Kasus: Magister Manajemen Universitas Muhammadiyah Yogyakarta) - YULIANA, YULIANA (Jurnal Bisnis Teori & Implementasi)
This study discusses the presence of: (1) The influence of emotional intelligence on performance management master program management graduate Master of Management, University of Muhammadiyah Yogyakarta, (2) The influence of situational leadership skills to the performance of business Master of Management Graduate Program, University of Muhammadiyah Yogyakarta. The population in this study was student of class 34, class 35 and 36 as well as faculty and staff Master of Management Graduate Program, University of Muhammadiyah Yogyakarta. In this study using survey method is the method of collecting primary data by asking questions to respondents and data collection tool was a questionnaire with a population of 60 respondents / person. Tests conducted on questionnaires filled out by respondents using tools SPSS version 15.00 for windows.The results of this study incluaded that there is no significant relationship between emotional intelligence to the business performance of the Master of Management, University of Muhammadiyah Yogyakarta. and there is a significant relationship between situational leadership skills to the performance of business Management Master of Management University of Yogyakarta. In this study of emotional intelligence variables that affect the performance of business most dominant Master of Management, University of Muhammadiyah Yogyakarta.Keywords: emotional intelligence, situational leadership skills and performance